5-Chloro-3-cyclohexylsulfinyl-2-methyl-1-benzofuran - Choi, Hong Dae (International Union of Crystallography, 2011)
There are two independent molecules in the asymmetric unit of the title compound, C(15)H(17)ClO(2)S, in each of which the cyclohexyl rings adopt chair conformations. In the crystal, molecules are linked by weak intermolecular C—H⋯O hydrogen bonds.